2014
DOI: 10.1007/s10120-014-0352-4
|View full text |Cite
|
Sign up to set email alerts
|

Gastric carcinoma: stage migration by immunohistochemically detected lymph node micrometastases

Abstract: Background Immunohistochemically detected micrometastases of the regional lymph nodes in previously pN0-classified gastric cancer have been incorporated in the TNM staging system. This study aims to determine the incidence of such micrometastases in gastric carcinoma and to investigate their impact on stage grouping and prognosis. Methods Ninety-five patients with gastric carcinoma classified as pN0 by conventional histological examination were enrolled. All patients underwent gastric resection with regional l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Recently, a meta-analysis of observational studies about lymph nodes micrometastases of early and advanced gastric cancer showed that there is a positive correlation between lymph nodes micrometastases and an unfavorable surgical outcome in gastric cancer patients (9). However, Theresa et al (27) had been reported that immunohistostaining of regional lymph nodes in node-negative gastric cancer patients led to an increased detection of lymph nodes micrometastases with significant implications for the staging system, but there was no impact on the survival time of these patients. Previously in vitro research indicated that some of the isolated tumor cells will be regressed spontaneously upon resection of the primary tumor owing to the activity of natural killer cells, whereas micrometastases continued to proliferate and eventually grew into gross metastases (28).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a meta-analysis of observational studies about lymph nodes micrometastases of early and advanced gastric cancer showed that there is a positive correlation between lymph nodes micrometastases and an unfavorable surgical outcome in gastric cancer patients (9). However, Theresa et al (27) had been reported that immunohistostaining of regional lymph nodes in node-negative gastric cancer patients led to an increased detection of lymph nodes micrometastases with significant implications for the staging system, but there was no impact on the survival time of these patients. Previously in vitro research indicated that some of the isolated tumor cells will be regressed spontaneously upon resection of the primary tumor owing to the activity of natural killer cells, whereas micrometastases continued to proliferate and eventually grew into gross metastases (28).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is secondary to the loss of E-cadherin expression, a critical event occurring in diffuse type gastric carcinoma (56) which, decreasing intercellular adhesion, ultimately leads to tumor cell dissociation (57). The higher probability of micrometastasis and ITC occurrence in diffuse gastric cancer (50,55,56) potentially supports the importance of lymph node immunostaining in this cancer type. Although lymph nodes harboring IHC-detected micrometastasis are considered positive nodes in gastric carcinoma, their clinical impact is unclear (58).…”
Section: Micrometastasesmentioning
confidence: 99%
“…Various clinicopathologic parameters appear associated with the occurrence of micrometastases. IHC-detected lymph nodes micrometastases were found to be significantly more frequent in Lauren's diffuse histotype (53)(54)(55). This finding is secondary to the loss of E-cadherin expression, a critical event occurring in diffuse type gastric carcinoma (56) which, decreasing intercellular adhesion, ultimately leads to tumor cell dissociation (57).…”
Section: Micrometastasesmentioning
confidence: 99%
“…While some authors suggest micrometastasis association with tumor size, grade of histological differentiation (G2/G3) and Lauren´s diffuse histology 4 , 5 , 11 , 12 , 26 , these results didn´t find any differences in LN involvement with respect to these characteristic. However, was observed that in the CK-positive group tumor tends to be larger than in the CK-negative group (4.0 vs. 2.8 cm).…”
Section: Discussionmentioning
confidence: 66%